APLIKASI MULTI BANK SAMPAH BERBASIS WEB - Ardian Hermawansyah; Tristiyanto Tristiyanto; Rizky Prabowo (Jurnal Pepadun, 2022)
Material waste is unwanted residue after the end of a process. Waste reduction activities aim to make all levels of society, including the government, the business world and the wider community able to carry out activities to reduce, reuse, recycle (3R) through smart, efficient and programmatic efforts. The best solution to this problem is a waste bank. Waste Bank is a place for sorting and collecting waste that can be recycled and reused which has economic value. Waste bank work mechanisms such as sorting waste, submitting waste to waste banks, weighing waste, recording, selling the delivered waste are entered into a savings book and revenue sharing for the sale of waste between savers and implementers.The multi waste bank information system can help the waste bank work.The multi waste bank information system can be used by the waste bank for the publication of the location of the waste bank, data collection of waste bank customers, recording and archiving customer transaction data and helping the waste bank to find customers with the online customer registration feature. The multi waste bank information system is built on a web basis using the laravel framework. The method applied in the development of a multi bank waste information system uses the waterfall model. The multi waste bank information system has been successfully built by testing the system's functionality using black box testing and expert judgement. The results that the system can function according to user expectations and needs.